Legal Review of Outsourcing in Indonesia as a Form of Hidden Exploitation in Employment Relations - Arifuddin Muda Harahap; Mirza Nasution; Calvin (ISNU Nine-Star Multidisciplinary Journal, 2025)
This study examines the practice of outsourcing in Indonesia as a form of hidden exploitation in employment relationships. Initially intended to improve company efficiency and create workforce flexibility, outsourcing often creates serious problems related to the protection of workers' rights. Many outsourced workers face status uncertainty, inadequate wages, limited access to social security, and even discrimination compared to permanent workers. These conditions demonstrate the potential for exploitation that contradicts the principles of social justice as mandated by the 1945 Constitution of the Republic of Indonesia and labor norms. The research method used is a normative juridical approach with a statutory and conceptual approach. Legal sources include primary legal materials in the form of relevant laws and regulations, particularly Law Number 13 of 2003 concerning Manpower and its amendments, Constitutional Court Decisions, and other derivative regulations. Secondary legal materials in the form of doctrine, labor law literature, and previous research findings are used to enrich the analysis. The results indicate that outsourcing regulations in Indonesia still leave room for ambiguity that companies can exploit to oppress workers. Inconsistencies between laws, government regulations, and on-the-ground practices weaken workers' bargaining power. This research confirms that outsourcing practices that fail to address worker protection principles have the potential to become a form of hidden exploitation, necessitating consistent law enforcement and the formulation of policies that better support social justice and worker welfare.